Analisis Gratifikasi dalam Belanja Online pada E-Commerce menggunakan Teori Uses and Gratification - Basuki, Syarifah Parameswara; Ovalia, Fira Magfira (Avant Garde, 2023)
Technology nowadays has been massively developed especially in the online business market, these activities showed the increased number of activities that can be done online or virtually. It started due to the pandemic in 2020 affected the habits to slowly shifted Indonesian markets to adapts and changed them to be an active online user. Nowadays all activities are mostly done online, so the business activities adapt to these changes. Indonesia is one of the countries that had the phenomenon of online shopping especially on E-Commerce or known as doing transactions through internet connection, so there are platforms that compete to make shopping experience and fulfill the needs of the users. This research is descriptive research with literature review method. The author will search for literature sources and books that are relevant with the related topic. The literature that will be used are the latest 10 years published literature with the background of Uses and Gratification theory, focused on the gratification concept that are expected by the audience and the assumptions of the theory itself. The goal is to dig more about the gratifications obtained from the satisfaction of online shopping. The results shows that consumers chose to shop online and influenced by several factors that consists of trust, convenience, price, and the entertainment that the platform gave. The result of this research could be a reference to the future research and enriched with other concepts of the Uses and Gratification Theory.